Optimization of cutting parameter for machining Ti-6Al-4V titanium alloy - Noor Danish, N. H. D.; Musfirah, Abdul Hadi (Penerbit UMP, 2022)
Titanium alloy Ti-6Al-4V, has been broadly used in industries, primarily medical manufacturing, and aerospace, due to their considerable mechanical properties. Aerospace structural components made of titanium alloy (Ti-6Al-4V) material, a difficult-to-machine material which results in massive cutting force, steep cutting temperature, and significant tool wear. In this research, carbide insert tool is used to cut a Ti-6Al-4V titanium block at constant depth of cut of 0.50 mm using the method of dry machining is investigated with the aim of estimating the effects of two manipulated cutting parameters, which are spindle speed (140 and 150 m/min), and feed rate (0.1 and 0.2). This was done to observe their effects on the tool wear of the insert. The objective of this study is to study the machinability performance of coated carbide insert tool under dry machining condition, and to optimize the cutting parameter to machine Ti-6Al-4V using dry machining method. It was found in this research that lowest valued parameter, Parameter 1 (140 m/min, 0.1 mm/rev) caused the most flank wear, and the roughest surface on the Ti-6Al-4V block. Lower speeds can possibly inflict higher shocking force, which leads to higher wear propagation.